2015
DOI: 10.1016/j.jcin.2014.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Regurgitation Is Associated With Increased Risk of Mortality in Patients With Low-Flow Low-Gradient Aortic Stenosis and Reduced Ejection Fraction

Abstract: OBJECTIVES This study sought to examine the impact of tricuspid regurgitation (TR) on mortality in patients with low-flow, low-gradient (LF-LG) aortic stenosis (AS) and reduced left ventricular ejection fraction (LVEF).BACKGROUND TR is often observed in patients with LF-LG AS and low LVEF, but its impact on prognosis remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 30 publications
1
28
0
2
Order By: Relevance
“…Furthermore, in a recent study including patients with end stage of heart failure, RV free wall strain was, among all echocardiographic parameters of RV function, the one that best correlated with the extent of RV myocardial fibrosis and patient's exercise capacity 32. In a recent study, we reported that the presence of >mild tricuspid regurgitation is associated with increased risk of mortality in patients with LF-LG AS 33. In the present study, we found that reduced RVLS is associated with increased risk of mortality.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, in a recent study including patients with end stage of heart failure, RV free wall strain was, among all echocardiographic parameters of RV function, the one that best correlated with the extent of RV myocardial fibrosis and patient's exercise capacity 32. In a recent study, we reported that the presence of >mild tricuspid regurgitation is associated with increased risk of mortality in patients with LF-LG AS 33. In the present study, we found that reduced RVLS is associated with increased risk of mortality.…”
Section: Discussionmentioning
confidence: 86%
“…S evere tricuspid regurgitation (TR) is prevalent and negatively affects long-term outcomes. [1][2][3][4][5] However, TR remains undertreated because of the high morbidity and mortality associated with tricuspid valve (TV) surgery. [6][7][8][9][10] Nevertheless, recent developments in the field of transcatheter valve interventions have stimulated a renewed interest in the "forgotten" TV.…”
mentioning
confidence: 99%
“…In developed countries, the most common tricuspid valve lesion is secondary TR which is highly prevalent in patients presenting with leftside valve disease ( Figure 2) [26]. Many studies suggest that the severity of TR, both isolated or in the presence of leftsided valvular disease, is associated with reduced exercise capacity, long-term mortality and reduced postoperative survival [27,28]. The severity of TR is highly sensitive to changes in loading conditions, and the absence of regurgitation at the time of treatment of the left-sided valve lesion does not guarantee long-term freedom from it.…”
Section: Tricuspid Valve Lesion With Left-sided Valve Diseasementioning
confidence: 99%